MODEL PENGELOLAAN DAERAH ALIRAN SUNGAI TERPADU (SUB DAS TAPUNG KANAN) - Harlon Sofyan; Thamrin Thamrin; Mubarak Mubarak (Jurnal Ilmu Lingkungan, 2015)
This study was conducted from March to May 2014. Locations research was conductedin Koto Garo district of Kampar. This study aims to identify management problems thatexist in the sub-watershed Tapung Kanan and analyze problems and problem resolutionsub-watershed management Tapung Kanan using Logical Framework Analysis (LFA)models. Based on the results obtained as follows: (1). Sub-watershed managementissues in Tapung Kanan based inventory data obtained from the implementation offocus group discussion between the sub-watershed communities around Tapung Kanan,NGOs, Provincial Government of Riau and Riau University Environment Rona namely:a). The potential threat of flooding and pollution of the environment in Sub-watershedTapung Kanan, b). The high land conversion practices were not in accordance withtheir distribution as well as the practice of forest destruction, c). The potential conflictsof management of natural resources is not optimal due to spatial synchronizationacross districts, d). The limited attention and public participation in environmentalconservation around the sub watershed Tapung Kanan, e). Not optimal performance forthe designated institutional sub-watershed management Tapung Kanan. (2). TapungKanan sub watershed management in an integrated manner using a model of LFA canmap problems and problem resolution. So that management can be realized gradually,then setting goals, objectives and strategies should be drawn up so that the next can bederived in the policies, programs, activities and location implemented. The resultingmanagement objectives in this study is "Realizing the Tapung Kanan sub watershed asone buffer region Ecosystem in Riau Province ".